ACE inhibitor spirapril effects on circadian blood pressure profile, quality of life, and psychological status in patients with Stage I-II arterial hypertension - V. M. Gorbunov; M. I. Smirnova; G. F. Andreeva; A. D. Deev (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To compare spirapril and amlodipine effects on circadian blood pressure (BP) profile, quality of life (QoL), and psychological status (PS) in patients with arterial hypertension (AH).Material and methods. This open, randomized, comparative crossover study (spirapril and amlodipine courses lasting for 4 weeks each) included 24 patients with Stage I-II AH (mean age 54,2 10,5 years; mean AH duration 12,3 10,2 years). After 7 days of no antihypertensive therapy, the participants were randomly assigned either spirapril (6 mg/d) or amlodipine (5 mg/d). In case of inadequate effectiveness, hydrochlorothiazide (25 mg) was added and/or amlodipine dose was increased to 10 mg/d; spirapril dose was unchanged. Twenty-four BP monitoring (BPM), PS and QoL assessment (MMPI, Marburg University Questionnaire) were performed. Statistical analysis was performed in SAS 6.12.Results. Mean BP level was achieved for both medications; individual target BP levels were achieved in 17 patients receiving spirapril and 18 participants receiving amlodipine. No significant difference was observed for main 24-hour BPM parameters. Spirapril was more effective in reducing nighttime BP. Effect uniformity was similar for both agents: systolic/diastolic BP smoothness index was 0,55/0,45 (р 0,05) for spirapril and 0,65/0,56 (р 0,05) for amlodipine. Both medications did not affect QoL or PS in AH patients. Spirapril also improved socialisation, self-control, optimism, and general energy level.Conclusion. Spirapril is a highly effective antihypertensive medication, improving not only circadian BP profile, but also PS parameters among AH patients.